Analisis Pengaruh Sales Growth Dan Firm Size Terhadap Nilai Perusahaan Pada PT.Primarindo Asia Infrastruktur Tbk - Elfan Muhamad Alfarizi; Aris Munandar; Aliah Pratiwi (Universitas Dian Nuswantoro, 2023)
This study aims to examine the effect of sales growth and firm size on firm value. This type of research includes quantitative research using secondary data obtained from the analysis of financial statements on the website www.idx.co.id. The population in this research is the financial statements of PT. Primarindo Asia Infrastructure Tbk for 12 years (2013-2023). The method used in selecting the sample was purposive sampling and determining the sample based on the criteria set by the researcher with a 10-year sample. Based on secondary results of data processing using multiple linear regression analysis, F test, t test, it is known that sales growth and firm size simultaneously have a significant effect on firm value. Partially, the results of this study indicate that the sales growth variable has no positive and significant effect on firm value. Meanwhile, firm size has a negative and significant effect on firm value. Sales growth and company size have a positive and significant effect on firm value.